Cyclical long-term development of complex technologies: Premature expectations in nanotechnology? - Ulrich Schmoch; Axel Thielmann (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2012)
After many years of tremendous growth, the patent activities in nanotechnology have slightly decreased and the growth of publication numbers in this field is slowing down. With these patterns nanotechnology exhibits typical characteristics of the cyclical de-velopment of complex science-based technologies which may be labelled double-boom development. However, the decrease of patents should not be interpreted as the end of the growth of nanotechnology, but rather as an intermediate stagnation before a second steep growth. This intermediate period will probably be short compared to other science-based technologies, as cognitive bottlenecks are largely compensated by a strong market pull and substantial public support from the science side.
urn:nbn:de:0011-n-1988162
Keywords: 330; Nanotechnologie; Patent; Publikationsanalyse; Wachstumsbranche